1996
DOI: 10.1093/ajcp/106.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Sialolithiasis:Differential Diagnostic Problems in Fine-Needle Aspiration Cytology

Abstract: Sialolithiasis with obstruction of major salivary gland ducts can lead to clinical tumefaction related to cystic dilatation. In addition to mucus accumulation, these pseudoneoplasms feature hyperplasia and squamous metaplasia of the ductal lining epithelium, with varying degrees of inflammation. The authors report five examples of this lesion aspirated from two males and three females ranging in age from 45 to 80 years (median 65 years). Three were in the submaxillary gland, and two were in the parotid. In thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 9 publications
1
10
0
2
Order By: Relevance
“…A particular case of the more generally described duct-obstructive lesion is sialolithiasis (23). The typical patient is female and has a submandibular gland swelling.…”
Section: Cystic Salivary Gland Aspiratesmentioning
confidence: 99%
“…A particular case of the more generally described duct-obstructive lesion is sialolithiasis (23). The typical patient is female and has a submandibular gland swelling.…”
Section: Cystic Salivary Gland Aspiratesmentioning
confidence: 99%
“…40 In these cases the smears can demonstrate immature squamous metaplastic elements that strongly resemble the "intermediate" cells of low grade mucoepidermoid carcinoma. 41 Therefore, it is suggested that when FNAB findings consistent with a low grade mucoepidermoid carcinoma are encountered, the possibility of sialolithiasis should be considered. Not all cases will show stones in cytologic material or radiographs, and further clinical investigation may be warranted before the institution of surgical therapy.…”
Section: Ab C Dmentioning
confidence: 99%
“…Sparse cellularity seen in cases of low-grade MEC has been reported. 19,20 In contrast, aspirates from high-grade MEC generally show marked cytologic atypia, at times precluding the correct characterization of the tumor. 4 -6,9 Occasionally, other malignant neoplasms that typically affect major salivary glands may arise in the minor salivary glands of the floor of the mouth and tongue and may be cystic.…”
Section: Discussionmentioning
confidence: 99%